Immunohistochemical study of E-cadherin and β-catenin expression in colorectal carcinomas - Özgüven, Banu Yilmaz; Karaçetin, Didem; Kabukçuoğlu, Fevziye; Taşkin, Tuğba; Yener, Şenay (Polish Journal of Pathology, 2011)
Parameters of histological type, differentiation, lymph node metastasis and stage have been observed to indicate the prognosis of colorectal carcinomas. Immunohistochemically E-cadherin and β -catenin expression of tumour cells have been evaluated to define life expectancy, response to the treatment, metastatic disease and recurrence of tumour in correlation with these prognostic parameters. 60 cases diagnosed as colorectal adenocarcinoma were selected to be studied retrospectively. Immunohistochemistry was performed using E-cadherin and β -catenin primary antibodies and avidin-biotin-peroxidase. 53 of 60 adenocarcinoma tissues were evaluated as classical type adenocarcinoma and 7 of them as mucinous carcinoma. 48 classical type adenocarcinoma tissues showed membranous staining for E-cadherin, 13 tissues showed cytoplasmic staining. All 53 adenocarcinoma tissues expressed nuclear or membranous type β -catenin in different intensities. Reduced E-cadherin expression significantly correlated with lymph nodes metastasis (p = 0.01). E-cadherin expression significantly correlated with increasing histological differentiation (p = 0.04). When E-cadherin and β -catenin expressions were compared, there was a significant difference between the tumour stage, histological differentiation and the existence of lymph node metastasis. When both E-cadherin and β -catenin expressions were reduced, there was a significant unfavourable prognosis.